Pengaruh Pendekatan RME terhadap Kemampuan Pemecahan Masalah Siswa pada Materi Operasi Hitung Campuran di Kelas IV SD IT Adzkia I Padang - Asrina Mulyati (Universitas Syiah Kuala, 2017)
The purpose of this research is to know the effect of using RME approach in problem solving process on mixed calculation material in class IV SD IT Adzkia I Padang. This research is a quantitative research with the static group comparizon design: randomized control group only design. The population of this research are all the fourth grade students of SDIT Adzkia I Padang. The sample of this research are khandaq 1 class and Khandaq 3 class with 56 students. Data were obtained through learning observation sheets, preliminary tests, and final tests. From the analysis of the data, it is found that there is a significant result of students problem solving skill in mixed calculation material problems in Class IV SD IT Adzkia I Padang. It can be seen from the test of the research hypothesis t-count = 3.003 greater than t-table = 1.67356 at the real level = 0.05.